Mothering Patterns With Stunting Toddlers Among The Age Of 24-59 Months - Nur Afni; Aminah Aatinaa Adhyatma; Indah Mastikana (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Nutrition still become major issues in Indonesia, one which is stunting. Stunting occurs due to lack of nutritional intake in toddlers, especially during the first 1000 days of life (HPK). As an effort to prevent stunting, it is necessary to address its factors, one of which is maternal parenting. This research sought to provide an overview regarding maternal parenting with the incidence of stunting toddlers aged 24-59 months in Kampung Tua, Tanjung Piayu Laut village Batam City. This qualitative research employed a descriptive method, involving 30 mothers who had stunting toddlers aged 24-59 months in KampungTua, Tanjung Piayu Laut. The measuring instrument used in this research was a questionnaire on maternal parenting, filled out directly by mothers who had stunting toddlers. The data analysis was carried out univariately to find out how description of mother’s parenting for stunting toddlers. The results showed that mothers with feeding practices in the good category were 14 people (46.7%), psychosocial stimulation in the good category were 24 people (80%), hygiene practices were in the good category as many as 27 people (90%) and environmental sanitation in the good category as many as 14 people (46.7%). Therefore, it can be concluded that of the four indicator of maternal parenting, feeding practices and environmental sanitation are still in the poor category.